2017
DOI: 10.4103/ijri.ijri_367_16
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic radiograph in skeletal dysplasias: An approach

Abstract: The bony pelvis is constituted by the ilium, ischium, pubis, and sacrum. The pelvic radiograph is an important component of the skeletal survey performed in suspected skeletal dysplasia. Most of the common skeletal dysplasias have either minor or major radiological abnormalities; hence, knowledge of the normal radiological appearance of bony pelvis is vital for recognizing the early signs of various skeletal dysplasias. This article discusses many common and some uncommon radiological findings on pelvic radiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…However, the effectiveness of ultrasonic examination ranges from 40 to 60%, and so the use of ultrasound alone does not suffice to comprehensively diagnose some abnormalities, such as a narrow thorax. When any skeletal dysplasia is suspected, diagnostic imaging using radiography [ 21 ], ultrasonography [ 23 ], computed tomography [ 34 ], and magnetic resonance imaging [ 1 , 11 , 30 ] is essential. Victoria et al [ 32 ] and Cassart et al [ 8 ] demonstrated a higher diagnostic precision using 3D CT compared to 2D ultrasound in skeletal dysplasias.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effectiveness of ultrasonic examination ranges from 40 to 60%, and so the use of ultrasound alone does not suffice to comprehensively diagnose some abnormalities, such as a narrow thorax. When any skeletal dysplasia is suspected, diagnostic imaging using radiography [ 21 ], ultrasonography [ 23 ], computed tomography [ 34 ], and magnetic resonance imaging [ 1 , 11 , 30 ] is essential. Victoria et al [ 32 ] and Cassart et al [ 8 ] demonstrated a higher diagnostic precision using 3D CT compared to 2D ultrasound in skeletal dysplasias.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effectiveness of this examination ranges from 40 to 60%, thus using only ultrasound is not sufficient to make a comprehensive diagnosis. When skeletal dysplasia is suspected, diagnostic imaging with the use of radiographic [ 15 ] and computed tomography [ 3 ] techniques is essential. In skeletodysplasias 3D-CT is superior to 2D-US [ 7 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…If skeletal dysplasia is suspected, using only ultrasound is not sufficient to make a comprehensive diagnosis. In such cases, the following four methods should be employed: radiographic examination [ 14 ], ultrasound imaging [ 12 ], CT [ 3 , 4 ] and MRI [ 9 ]. Van Zalen-Sprock et al [ 21 ] compared the sensitivity of imaging methods in detecting ossification centers in the fetal skeleton.…”
Section: Discussionmentioning
confidence: 99%